PARTISIPASI MASYARAKAT PEMAKAI AIR DALAM OPERASI DAN PEMELIHARAAN EMBUNG DI KABUPATEN KARANGASEM - I G. Oka Wiradnyana; I N. Norken; I G. B. Sila Dharma (JURNAL SPEKTRAN, 2013)
Karangasem regency is one area of dry areas in the province of Bali. This area has limited surface water resources in some area, and the rivers are partly a intermittent, which there is no water in the dry season, so as to meet the needs of raw water is very difficult. One alternative to overcome this, the government has built the small reservoir, called the Embung. In order to meet the embung system sustainable, the participation of water users in the operation and maintenance of Embung is required. This research aims to determine the influence of human resources (HR) factors, funding, ideas and effort, and organization in the operation and maintenance of Embung. Number of samples obtained in these research as many as 290 respondents is calculated by Slovin theory formulation of the total 1.045 family heads of water user population. Community participation is measured statistically using the independent variables, namely human resources (X1), funding (X2), ideas and effort (X3), organization (X4), as well as the operation and maintenance of embung as the dependent variable (Y). Data results of the questionnaire, scored into a Likert scale, further processing was carried out by multiple linear regression analysis. using statistical software Statistical Package for Social Science (SPSS) version 19. The results showed that there is participation of water user in the operation and maintenance of embung in the regency of Karangasem, which can be shown from the resulting regression equation model, where all the regression coefficients of each variable are positive. Independen variables also have a significant influence on the dependent variable, with Fhitung (= 2316,926) > Ftabel (= 1,96). While the most dominant variable effects on the operation and maintenance of embung is organization's variable, with the ? value of 0.382, followed by ideas and effort variable (? = 0.329), proceeded by funding (? = 0.302), and the lowest is the human resources (HR) variable (for ? = 0.283)